Size, diversification and risk: Preliminary evidence from commercial banks in Pakistan - Ayesha Afzal; Nawazish Mirza (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
The aim of this paper is to provide some preliminary evidence on relation between size, diversification and risk in commercial banks of Pakistan. Using a panel of Pakistani banks, we investigated whether bigger banks are better diversified than smaller banks. The results suggested that larger banks were more diversified than their smaller counterparts mainly on account of their outreach and size of credit portfolio. On the risk side, based on accounting and market based risk measures, we explored if there is any impact of diversification on risk. We could not deduce significant result in favor of accounting risk measure of impaired lending signaling that banks find no incentive in diversification of credit books. The market based measures of VaR and Default indicator were significantly related to diversification signifying that market participants consider diversification as a relevant tool for risk mitigation. These findings have policy implications for regulators and risk management to ensure stability in financial system.
Keywords: 330; Banking risks; Size; Diversification; Financial system; Bankgeschäft; Bankrisiko; Portfolio-Management; Bankenkrise; Pakistan